Analisis E-WOM (Electronic Word of Mouth) bagi Konsumen dalam Pembelian Notebook di Situs Belanja Online - Aulia Iefan Datya; Wayan Weda Asmara Dewi (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
This paper discusses the behavior of consumers to seek and receive information in electronic form of Word of Mouth (E-WOM). Currently, e-WOM is considered as a part of electronic advertising or e-commerce, e-commerce is included in various aspects of business activities for online products and services transactions. Nowadays, online shopping site act as a core of all forms of e-commerce transactions, where many parties interact electronically rather than doing direct or physically business transactions. The development of information technology makes notebook as a devices to supporting performance and works. This makes notebooks as one of high-demanded, quite interesting and top purchase products in the online shopping sites. Qualitative descriptive study was conducted to determine the factors that are important to consumers when choosing these notebooks products on the renowned and leading online shopping sites based on the reviews displayed in the product pages at online sales site, especially notebooks.